El origen del derecho administrativo en México - Fernández Ruíz, Jorge (UNIVERSIDAD DE SONORA, 2021)
This document addresses the fascinating issue of the origin of Administrative Law, in Mexico, its legislation, its main institutions, and the authors that mark its trajectory from the 19th century through the 20th century to the present day, the beginning of the third decade of the XXI century.